PELAKSANAAN PERJANJIAN KREDIT MIKRO DENGAN JAMINAN UMUM PADA PT. BANK MANDIRI (PERSERO) TBK CABANG SUMENEP - Mohammad Anwar; Bambang Hermanto (Journal MISSY (Management and Business Strategy), 2022)
The collapse of this sector will be able to cause a big shock to the state of the national economy. In accordance with article 8 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning banking which states that in providing credit or financing based on Sharia principles, commercial banks are required to have confidence based on in-depth analysis of the intentions and abilities and abilities of debtor customers. to pay off the debt or return the financing as promised and commercial banks are required to have and apply credit and financing guidelines based on Sharia principles, in accordance with the provisions stipulated by Bank Indonesia. The process of granting micro credit to PT. Bank Mandiri (Persero) Tbk. Sumenep Branch, the Bank must conduct an in-depth analysis of the prospective debtor on the debtor's ability/ability to repay all his debts in accordance with the agreed terms. In the implementation of micro credit agreements with general guarantees, where the debtor must pay installments of principal and interest in accordance with what was agreed with the Bank and maintain / protect the goods that have been guaranteed for the sake of smooth credit that has been given by the Bank to the debtor. Rescue efforts and settlement methods in the event of bad credit, the Bank must reschedule (rescheduling), reconditioning and restructuring. Because the amount of credit given is small, the settlement through KP2LN or the District Court does not need to be done. It is enough to take a family approach, allow for extension of credit repayment period, and perform write-offs (establishment of allowance for earning assets write-off).